Whole Chromosome 7 Gain Predicts Higher Risk of Recurrence in Pediatric Pilocytic Astrocytomas Independently From KIAA1549-BRAF Fusion Status. Issue 4 (April 2016) - Roth, Jacquelyn J.; Fierst, Tamara M.; Waanders, Angela J.; Yimei, Li; Biegel, Jaclyn A.; Santi, Mariarita
Abstract : The most frequent genetic alteration identified in pediatric pilocytic astrocytomas and pilomyxoid variant is the KIAA1549-BRAF fusion, which typically results from a 2.0 Mb tandem duplication in chromosome band 7q34. Less frequent abnormalities include fusion genes, BRAF, FGFR, KRAS, and NF1 point mutations, and whole chromosome gains. To correlate genetic alterations with clinical course data, we retrospectively analyzed the tumors with pilocytic and pilomyxoid histology of a cohort of 116 pediatric patients, aged 5 months to 23 years. Gross total resection was associated with a decreased risk of recurrence (p = 0.001), supporting previous findings that complete tumor excision correlates with long-term and disease-free survival. We found no significant association between recurrence rate and the presence of the KIAA1549-BRAF fusion or BRAF mutation (p = 0.167). Interestingly, gain of whole chromosome 7 (WC7) was associated with a 4.7-fold increased risk of tumor recurrence, even after adjusting for surgical status (p = 0.025), and other genetic alterations. Using fluorescence in situ hybridization, we demonstrated that when WC7 gain accompanies the KIAA1549 - BRAF fusion, the fusion likely arises first. This study highlights the utility of genetic studies for risk assessment of pilocytic and pilomyxoid astrocytomas, which may impact treatment selections.